DESENVOLVIMENTO DE SISTEMA DE CLASSIFICAÇÃO PARA QUALIDADE DE BLOQUEIO NEUROMUSCULAR EM PACIENTES SUBMETIDOS A ELETROCONVULSOTERAPIA SOB ANESTESIA - MENDES, Matheus Veras Guterres (2024)
The anesthesiologist's participation in Electroconvulsive Therapy (ECT) led to a paradigm shift regarding the safety of the procedure. The use of hypnotic agents and neuromuscular blockers not only reduced complications, but also allowed greater patient satisfaction with their treatment. Although adequate control of the motor response resulting from the induction of tonic-clonic seizures by ECT is a fundamental part of anesthetic care, to date, no classification has been proposed that takes into account clinical care parameters that define which level of blockade is considered the most appropriate to allow ECT to be performed. This study aimed to create a classification system that has the possibility of practically determining the levels of attenuation of the motor response that are suitable for electroconvulsive therapy. This is a methodological study to develop an instrument to evaluate the quality of neuromuscular blockade in patients undergoing electroconvulsive therapy under anesthesia. Content validation was carried out through consultation with a panel of experts composed of Anesthesiologists and Psychiatrists, working in ECT using modified Delphi methodology, through an electronic questionnaire (Google Forms). Based on the experts' responses, the Content Validity Index (CVI) was calculated. Items that obtained CVI ≥ 0.70 were kept in the instrument. To determine the most important items, Principal Component Analysis (PCA) was performed. The final version of the instrument was subjected to an internal consistency analysis using Cronbach's Alpha coefficient. In the content validation stage, all eight items evaluated presented a CVI greater than 0.7. After the Principal Component Analysis (PCA), the final scale proposed pre stimulus had 4 items: “apparent immobility”, “reduction in muscle tone”, “absence of eye opening to verbal commands” and “abolition of the corneal- eyelid; the item “memory of the event or perception of shortness of breath absent upon awakening”, as it consists of a post electrical stimulus assessment, was included for guidance regarding the dose of drugs for each patient's subsequent ECT sessions. The scale was considered adequate in the reliability analysis using Cronbach's alpha, which presented a coefficient of 0.79. The elaborated scale presented valid content according to expert analysis, as well as adequate internal consistency in the assessment of reliability using Cronbach's alpha.